MENATA TUGAS KELOMPOK SADAR WISATA (POKDARWIS) SUKODONO DENGAN PENDEKATAN ANALISIS JABATAN - Resmiatini, Erna; Asmoro, Bramantyo Tri (E-Jurnal Manajemen; Vol 9 No 11 (2020)DO - 10.24843/EJMUNUD.2020.v09.i11.p04, 2020)
This research is a n applied research focused on solving problems experienced by the Sukodono Tourism Awareness Group (Pokdarwis). The results of preliminary observations showed that they did not understand the tasks to be carried out. Therefore, this study aims to analyze and compile job descriptions of Pokdarwis Sukodono. The method used is a descriptive qualitative method, with a job analysis approach that adapts the steps of Dessler's (2010) job analysis and qualitative data analysis by Miles & Huberman's model (1994) . Meanwhile, the data collection techniques in this study were interviews, observation, and documentation. The result obtained is job description of Pokdarwis Sukodono starting from the Chairman to the Business Development Section. This result is obtained after conducting repeated job analysis to obtain a credible job description. The results of this study bring enormous benefits to the management of Pokdarwis Sukodono, because now the management has a clear duty reference in working as a tourism agent in their area. Keywords: Job Analysis; Job Description; Pokdarwis.